Implementation of the Repetitive Method in Teaching Clean and Healthy Living Behaviors for Early Childhood - Ahmad Maududi (Formad English Foundation NTB-Jakarta, 2026)
Clean and Healthy Living Behaviors (PHBS) in early childhood are essential for supporting children’s health, independence, and the formation of lifelong healthy habits. At RA Daruttaqwa Teko, initial observations indicated that several children were not consistently practicing key PHBS behaviors, such as washing hands properly, using soap, disposing of waste appropriately, and covering the mouth when coughing or sneezing. This study aimed to improve children’s PHBS through the implementation of the repetitive method. The research employed Classroom Action Research involving 15 children as participants. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through systematic observation of PHBS indicators using a developmental scale categorized as BB (Not Yet Developed), MB (Beginning to Develop), BSH (Developing as Expected), and BSB (Very Well Developed), and were analyzed using descriptive quantitative techniques. The results showed a significant improvement across all PHBS indicators from the pre-cycle to Cycle II. Children demonstrated increased independence, consistency, and internalization of clean and healthy living behaviors, with several children even becoming positive role models for their peers. The findings confirm that the repetitive method is effective in strengthening habit formation and promoting sustainable health behaviors in early childhood. Therefore, it is recommended as a routine instructional strategy for PHBS learning in early childhood education settings to support long-term behavioral development.